Changes in Community Behavior Regarding Cardiovascular Health and Hypertension After Participating in Prolanis Activities Literature Review - Dina Rahmah Fajriana; Budi Aji; Joko Mulyanto (Poltanesa, 2025)
The Chronic Disease Prevention and Management Program (Prolanis) has become one of the main strategies in efforts to increase public awareness of cardiovascular health and reduce the prevalence of hypertension. This study aims to present a literature review regarding the impact of the Prolanis program on changing people's behavior regarding cardiovascular health and hypertension management. The literature search method was carried out through various online databases using relevant keywords. The results of literature analysis show that the Prolanis program has consistently proven effective in increasing public knowledge about cardiovascular risk factors, motivating changes in healthy behavior such as balanced eating patterns and increasing physical activity, as well as increasing compliance with treatment and monitoring of hypertension conditions. These findings highlight the important role of the Prolanis program in changing people's behavior towards a healthier lifestyle and better management of hypertension. The implications of the results of this literature include the need for wider development and implementation of the Prolanis program as well as ongoing evaluation to ensure its sustainability and effectiveness in overcoming cardiovascular health problems and hypertension at the community level.Systematic review research is a way in the research process to find the best results from previous research to search for literature systematically and then analyze and conclude using the data prism method flow from the results of literature data analysis to answer problems effectively and significantly. The data that has been collected from this data collection method is then processed and combined to obtain related explanationsThe impact of the Healthy Elderly Program (Prolanis) on changes in community behavior in relation to cardiovascular health and controlling hypertension.